Toxic Inequities: The Global Health Burden of Pesticide Exports to Low- and Middle-Income Countries - Steven Shin; Haejin Jung (GHMJ (Global Health Management Journal), 2025)
Background: The continued export of banned pesticides from high-income countries (HICs) to low- and middle-income countries (LMICs) remains a critical yet under-addressed global health issue. These hazardous chemicals are legally shipped to nations with weaker regulatory frameworks. As a result, workers and communities in LMICs face disproportionate exposure to toxic substances that contribute to acute poisoning, developmental disorders, and chronic disease. Aims: This paper examines the international trade of banned pesticides through view of global health equity and frames these practices as a form of structural violence that endangers LMIC populations and violates the right to health. Methods: This qualitative study uses document and policy analysis of international trade records, legal frameworks, and public health literature. It outlines the legal mechanisms and policy gaps, such as the weaknesses of the Rotterdam Convention and the permissiveness of export laws in the EU, U.S., and Switzerland that enable the ongoing flow of hazardous substances. Results: Pulling on case studies, epidemiological evidence, and international human rights frameworks, the paper investigates the health impacts of pesticide exposure and highlights the ethical failures related to current trade practices. Conclusion: Our synthesis foregrounds the research gap and advances a rights-based, structural-violence framing that clarifies the policy mandate. We suggest aligning export bans with domestic prohibitions, strengthening Rotterdam prior-informed-consent and enforcement, and financing transitions to IPM, biopesticides, and agroecology in LMIC supply chains.